2019
DOI: 10.3389/fbioe.2019.00123
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Variations in Thumb Position From Recordings of the Surface Electromyogram in Adults Performing Static Grips, a Proof of Concept Study

Abstract: Hand gesture and grip formations are produced by the muscle synergies arising between extrinsic and intrinsic hand muscles and many functional hand movements involve repositioning of the thumb relative to other digits. In this study we explored whether changes in thumb posture in able-body volunteers can be identified and classified from the modulation of forearm muscle surface-electromyography (sEMG) alone without reference to activity from the intrinsic musculature. In this proof-of-concept study, our goal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Due to its mathematical simplicity and good performance, time-domain (TD) features are commonly used [18]. TD features are determined based on the amplitude of the signals and do not require any complicated measurement and frequently used TD feature is Root Mean Square (RMS) [2,17] and mean absolute value [15,18], while frequency-domain (FD) characteristics are based on the frequency range and calculated based on the Fourier transformation and frequently features used are mean frequency [16,19] and median frequency [16,20]. The results of the study conducted by Siddiqi and Sidek [17] showed TD analysis produces higher accuracy to differentiate different finger attitudes than FD.…”
Section: Fig 2 -Thumb Extrinsic Musclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its mathematical simplicity and good performance, time-domain (TD) features are commonly used [18]. TD features are determined based on the amplitude of the signals and do not require any complicated measurement and frequently used TD feature is Root Mean Square (RMS) [2,17] and mean absolute value [15,18], while frequency-domain (FD) characteristics are based on the frequency range and calculated based on the Fourier transformation and frequently features used are mean frequency [16,19] and median frequency [16,20]. The results of the study conducted by Siddiqi and Sidek [17] showed TD analysis produces higher accuracy to differentiate different finger attitudes than FD.…”
Section: Fig 2 -Thumb Extrinsic Musclesmentioning
confidence: 99%
“…Previous studies have used various classifiers such as Neural Network (NN), Support Vector Machine (SVM), and Linear Discriminant Analysis (LDA). As the result, all the classifiers performance show accuracy above 89%, however, there is not a single best classifier as it depends on the data set [2,26]. The results of different classification algorithms are compared to find which algorithm produces effective results.…”
Section: Fig 2 -Thumb Extrinsic Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-stream networks have better generalization capabilities. The high variability of sEMG and the lack of existing data limit the application of gesture recognition technology Aranceta-Garza and Conway, 2019). In future work, high-density sEMG (Chen et al, 2020) and multiple information fusion will be the direction of dynamic gesture recognition research.…”
Section: Algorithmsmentioning
confidence: 99%
“…Therefore, each finger must be in the extended position and the thumb is forced to grip the side of the ball. Non-sports studies have reported that the position of the thumb changes the muscle activity of the flexor and extensor muscles of the forearm in simple grasping movements 11) . Different methods of holding the ball in baseball are affected by hand length and ball size and may influence the position of the thumb and the metacarpophalangeal joint (MP) angle.…”
Section: Introductionmentioning
confidence: 99%